Application of micro-nano iron-carbon composition in efficient reduction of hexavalent chromium in soil

Micro-nano iron carbon composition prepared by ball milling method solves the problems of complex operation, high cost and easy passivation of zero-valent iron when treating hexavalent chromium in soil in the prior art, and achieves efficient and economical Cr(VI) Removal effect has wide application prospects.

CN119387287APending Publication Date: 2025-02-07INST OF SOIL SCI CHINESE ACAD OF SCI
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411447259.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-16
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

The prior art has problems such as complex operation, high cost, and easy passivation and aggregation of zero-valent iron when dealing with hexavalent chromium in soil, which limits its widespreadness in large-scale production and application.

Method used

The ball milling method is used to mix commercially available 12μm activated carbon and micron-scale zero-valent iron not higher than 100μm at a specific mass ratio. Through the ball milling process of alternating forward and reverse rotation mode, micro-nano iron carbon with large specific surface area and high reactivity is prepared. Composition.

Benefits of technology

It realizes a zero-valent iron composite material with simple operation, low cost and easy to mass production, which significantly improves the adsorption effect and reduction ability of Cr(VI), and has good application value and promotion prospects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119387287A_ABST
    Figure CN119387287A_ABST
Patent Text Reader

Abstract

The invention discloses application of a micro-nano iron-carbon composition in efficient reduction of hexavalent chromium in soil. The preparation method of the micro-nano iron-carbon composition comprises the following steps: taking activated carbon and micron-sized zero-valent iron as raw materials, adding the activated carbon and the micron-sized zero-valent iron into a ball mill according to a mass ratio under a room temperature condition, performing ball milling on the raw materials in a positive and negative rotation alternate operation mode, and after the ball milling is completed, obtaining the micro-nano iron-carbon composition. And storing the obtained solid powder of the modified iron-carbon material in a centrifugal tube. The composite material modified by ball milling is large in specific surface area, high in reaction activity, simple in preparation method, low in cost and easy for large-scale production. The composite material can effectively reduce Cr (VI), and has good application value and popularization prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of environmentally friendly material preparation, and in particular to the application of a micro-nano iron-carbon composition in efficiently reducing hexavalent chromium in soil. Background Art

[0002] Metal Cr is an element closely related to human life and production. It is widely used in electroplating, printing and dyeing, metallurgy and other fields. However, due to the lack of environmental awareness or insufficient environmental protection measures, a large amount of chromium-containing wastewater or solid pollutants are discharged into the natural environment without harmless treatment. Among them, Cr (VI) has become an urgent task for environmental protection due to its high toxicity, difficulty in degradation and bioaccumulation.

[0003] In recent years, zero-valent iron (ZVI) has been widely used as an environmental remediation material with the advantages of large specific surface area, strong reducibility and high reactivity. Related studies have shown that the redox potential of ZVI is -0.44V and has strong reductive properties. Therefore, ZVI is widely used as an excellent electron donor to treat various toxic pollutants in water and soil. However, zero-valent iron also has certain limitations in practical applications, such as easy passivation and easy agglomeration, which limit the conditions for its use alone. In order to overcome these shortcomings, researchers have increased its reactivity by doping other metals (such as Pd, Cu, Al, etc.); they have also modified ZVI by surfactants or polymers or used carbon materials as ZVI carriers to enhance the reduction activity. Carbon materials have the advantages of high specific surface area, stable structure and low cost. The most commonly used carrier is activated carbon (AC). AC has a rich pore structure and a large specific surface area, which can significantly improve the dispersibility of zero-valent iron. In addition, the good adsorption capacity of activated carbon can accelerate the enrichment of pollutants, which is conducive to the contact between zero-valent iron and pollutants, so that adsorption and reduction can proceed simultaneously.

[0004] At present, the most widely used method for loading ZVI onto activated carbon is liquid phase reduction method, which is divided into one-step method and two-step method, but both are complicated to operate and costly, which is not conducive to large-scale production. Ball milling is a low-cost and simple loading method. Ball milling is a solid material that changes its crystal structure and physical and chemical properties under the action of mechanical forces such as friction, collision, impact, and shear, and can greatly increase the specific surface area of ​​solid particles and improve the activity of the material.

[0005] Therefore, the development of an activated carbon-loaded zero-valent iron composite material with simple technology, low cost and high safety has broad application prospects. Summary of the invention

[0006] The technical problem to be solved by the present invention is to provide an application of a micro-nano iron-carbon composition for the efficient reduction of hexavalent chromium in soil. The composite material modified by ball milling has a large specific surface area, high reaction activity, a simple preparation method, low cost, and is easy for large-scale production.

[0007] In order to solve the above technical problems, a technical solution adopted by the present invention is: to provide an application of a micro-nano iron-carbon composition in the efficient reduction of hexavalent chromium in soil.

[0008] In a preferred embodiment of the present invention, the method for preparing the micro-nano iron-carbon composition comprises the following steps: Using activated carbon and micron-sized zero-valent iron as raw materials, at room temperature, the activated carbon and micron-sized zero-valent iron are added into a ball mill according to a mass ratio, and the raw materials are ball-milled through a forward and reverse alternating operation mode. After the ball milling is completed, the solid powder of the modified iron-carbon material is stored in a centrifuge tube.

[0009] Furthermore, the activated carbon adopts commercially available 12 μm activated carbon, and the maximum particle size of the micron-sized zero-valent iron is not higher than 100 μm.

[0010] Furthermore, the activated carbon and micron-sized zero-valent iron are mixed in a mass ratio of 5:1.

[0011] Furthermore, the ball mill was operated for 12 hours, the rotation speed was 400 rpm, and the ball milling atmosphere was air.

[0012] Furthermore, during ball milling, the mass ratio of the ball milling beads to the ball milled material is 10:1.

[0013] Furthermore, the ball milling beads are made of zirconium oxide and have a diameter of 1-15 mm.

[0014] Furthermore, one alternating operation cycle of the forward and reverse alternating operation mode is forward rotation for 10 minutes and then reverse rotation for 10 minutes.

[0015] The beneficial effects of the present invention are as follows: the present invention uses commercially available 12 μm activated carbon and commercial zero-valent iron powder not higher than 100 μm as raw materials, and has the characteristics of simple operation, low cost, and easy large-scale production. At the same time, the activated carbon is loaded on zero-valent iron by ball milling process to prepare AC-ZVI composite material, and the large specific surface area of ​​activated carbon effectively improves the adsorption effect of the composite material on Cr(VI), and increases the mutual contact area between zero-valent iron and Cr(VI). Therefore, the composite material can effectively reduce Cr(VI), and has good application value and promotion prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 is a SEM image of the micro-nano iron-carbon composite prepared in Example 4; Figure 2 is the XRD pattern of the micro-nano iron-carbon composition prepared in Example 4; Figure 3 It is a graph showing the removal rate of the micro-nano iron-carbon composition prepared in Examples 1 to 5 on Cr (VI) contaminated soil; Figure 4 It is a comparison chart of the removal rate of Cr (VI) contaminated soil by the micro-nano iron-carbon composition prepared in Example 4 and Comparative Example 1; Figure 5 It is a graph showing the removal rate of the micro-nano iron-carbon composition prepared in Examples 1 to 5 for different types of Cr (VI) contaminated soil. DETAILED DESCRIPTION

[0017] The preferred embodiments of the present invention are described in detail below in conjunction with the accompanying drawings so that the advantages and features of the present invention can be more easily understood by those skilled in the art, thereby making a clearer and more definite definition of the protection scope of the present invention.

[0018] Embodiments of the present invention include: Embodiment 1: An application of a micro-nano iron-carbon composition in the efficient reduction of hexavalent chromium in soil, wherein the preparation method of the micro-nano iron-carbon composition comprises the following steps: Commercially available 12μm activated carbon and micron-grade zero-valent iron not higher than 100μm were used as raw materials. At room temperature, activated carbon and zero-valent iron were added to a ball mill at a mass ratio of 1:1. The raw materials were ball milled at a speed of 400rpm for 12 hours in a forward and reverse alternating operation mode. Zirconia balls with a diameter of 1-15mm were used as ball milling media, and the ball-to-material ratio used in ball milling was 20:1.

[0019] Embodiment 2: An application of a micro-nano iron-carbon composition in the efficient reduction of hexavalent chromium in soil, wherein the preparation method of the micro-nano iron-carbon composition comprises the following steps: Using commercially available 12μm activated carbon and micron-grade zero-valent iron not higher than 100μm as raw materials, activated carbon and zero-valent iron were added to a ball mill at a mass ratio of 2:1 at room temperature, and the raw materials were ball-milled at a speed of 400rpm for 12 hours in a forward and reverse alternating operation mode. Zirconia balls with a diameter of 1-15mm were selected as the ball-milling medium, and the ball-to-material ratio used in the ball milling was 20:1.

[0020] Embodiment 3: An application of a micro-nano iron-carbon composition in the efficient reduction of hexavalent chromium in soil, wherein the preparation method of the micro-nano iron-carbon composition comprises the following steps: Using commercially available 12μm activated carbon and micron-grade zero-valent iron not higher than 100μm as raw materials, activated carbon and zero-valent iron were added to a ball mill at a mass ratio of 3:1 at room temperature, and the raw materials were ball-milled at a speed of 400rpm for 12 hours in a forward and reverse alternating operation mode. Zirconia balls with a diameter of 1-15mm were selected as the ball-milling medium, and the ball-to-material ratio used in the ball milling was 20:1.

[0021] Embodiment 4: An application of a micro-nano iron-carbon composition in the efficient reduction of hexavalent chromium in soil, wherein the preparation method of the micro-nano iron-carbon composition comprises the following steps: Using commercially available 12μm activated carbon and micron-grade zero-valent iron not higher than 100μm as raw materials, activated carbon and zero-valent iron were added to a ball mill at a mass ratio of 5:1 at room temperature, and the raw materials were ball-milled at a speed of 400rpm for 12 hours in a forward and reverse alternating operation mode. Zirconia balls with a diameter of 1-15mm were selected as the ball-milling medium, and the ball-to-material ratio used in the ball milling was 20:1.

[0022] Embodiment 5: An application of a micro-nano iron-carbon composition in the efficient reduction of hexavalent chromium in soil, wherein the preparation method of the micro-nano iron-carbon composition comprises the following steps: Commercially available 12μm activated carbon and micron-grade zero-valent iron not higher than 100μm were used as raw materials. At room temperature, activated carbon and zero-valent iron were added to a ball mill at a mass ratio of 7:1. The raw materials were ball milled at a speed of 400rpm for 12 hours in a forward and reverse alternating operation mode. Zirconia balls with a diameter of 1-15mm were used as ball milling media, and the ball-to-material ratio used in ball milling was 20:1.

[0023] Comparative Example 1: Based on Example 4, the ratio of activated carbon to zero-valent iron in ball milling was changed to 1:5, and the other conditions remained unchanged. The structural characterization of the micro-nano iron-carbon composite prepared in Example 4 is illustrated in conjunction with the accompanying drawings: (1) The SEM image of the micro-nano iron-carbon composite synthesized in Example 4 is as follows Figure 1 As shown in the figure, the composite material forms a welded and overlapped surface morphology due to the collision and extrusion of the ball milling beads during the ball milling modification process.

[0024] (2) The XRD pattern of the micro-nano iron-carbon composite synthesized in Example 4 is as follows: Figure 2 As shown, the zero-valent iron peak on the surface of the composite material is significantly enhanced, and the surface material modification is successful.

[0025] The following test is conducted on the performance of the composite material prepared in the above embodiment in terms of efficient reduction of hexavalent chromium in soil in conjunction with the accompanying drawings: (1) The removal effect of composite materials with different iron-carbon ratios in Examples 1 to 5 on Cr(VI) in soil: This experiment was conducted at room temperature. 5g of 100mg / L Cr (VI) contaminated soil was added to a 50ml centrifuge tube. 100mg of the composite materials milled with different iron-carbon ratios in Examples 1 to 5 were added at the same time. 20ml of deionized water was added and the mixture was shaken on a shaker at 150rpm. After 24 hours of reaction, the soil sample was centrifuged and dried in a freeze dryer. The Cr (VI) concentration was determined by alkaline digestion method (EPA-3060 method). The results are shown in the figure. Figure 3 shown.

[0026] Depend on Figure 3 It can be seen that among the composite materials with different iron-carbon ratios synthesized in Examples 1 to 5, the composite material with an iron-carbon ratio of 1:5 has the best removal effect on Cr (VI) contaminated soil, and the removal rate reaches 96.31% after 24 hours of reaction.

[0027] (2) The removal effect of the composite materials with different iron-carbon ratios synthesized in Example 4 and Comparative Example 1 on Cr(VI) in water: This experiment was conducted at room temperature. 5g of 100mg / L Cr (VI) contaminated soil was added to a 50ml centrifuge tube. 100mg of the composite materials prepared by ball milling with different iron-carbon ratios in Example 4 and Comparative Example 1 were added. 20ml of deionized water was added and the mixture was shaken on a shaker at 150rpm. After centrifugation at a certain interval, soil samples were taken and dried in a freeze dryer. The Cr (VI) concentration was determined by alkaline digestion method (EPA-3060 method). The results are shown in the figure. Figure 4 shown.

[0028] Depend on Figure 4 It can be seen that the composite material prepared with an iron-carbon ratio of 1:5 has the best removal effect on Cr (VI) contaminated soil, and the removal rate can reach 93.64% after 16 hours of reaction.

[0029] (3) Example 4: Removal effect of Cr(VI) contaminated soil in different regions: This experiment was conducted at room temperature. 5g of 100mg / L Cr(VI) contaminated soil from different regions was added to a 50ml centrifuge tube. 100mg of the composite material prepared in Example 4 was added, and 20ml of deionized water was added. The reaction was shaken at 150rpm on a shaker. After 24 hours of reaction, the soil sample was centrifuged and dried in a freeze dryer. The Cr(VI) concentration was determined by alkaline digestion method (EPA-3060 method). The results are as follows: Figure 5 shown. Figure 5The corresponding relationship between the soil numbers and Cr (VI) contaminated soils in different regions is: 1. Lingtu brown soil in Mentougou, Beijing; 2. Hailun black soil in Heilongjiang; 3. Rice-dryland rotation in Xianning, Hubei; 4. Yellow-red soil in Dali, Yunnan; 5. High-calcium soil in Ningxia; 6. Black soil in Jilin; 7. Loess soil in Changwu, Shaanxi; 8. Red soil in Yingtan, Jiangxi.

[0030] Depend on Figure 5 It can be seen that among the removal effects of the composite material prepared in Example 4 on Cr (VI) contaminated soil in different regions, the high-calcium soil in Ningxia has the best effect, with a removal rate of up to 98.67% after 24 hours of reaction, while the black soil in Hailun, Heilongjiang has the worst effect, with a removal rate of only 66.85%, which may be related to the differences in soil organic matter content in different regions.

[0031] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered exemplary and non-limiting in all respects, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations falling within the meaning and scope of the equivalent elements of the claims be included in the invention. Any reference numeral in a claim should not be considered as limiting the claim to which it relates.

[0032] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

Claims

1. Application of a micro-nano iron-carbon composition in the efficient reduction of hexavalent chromium in soil.

2. The use according to claim 1, characterized in that: The preparation method of the micro-nano iron-carbon composition comprises the following steps: Using activated carbon and micron-sized zero-valent iron as raw materials, at room temperature, the activated carbon and micron-sized zero-valent iron are added into a ball mill according to a mass ratio, and the raw materials are ball-milled through a forward and reverse alternating operation mode. After the ball milling is completed, the solid powder of the modified iron-carbon material is stored in a centrifuge tube.

3. The use according to claim 2, characterized in that: The activated carbon is commercially available 12 μm activated carbon, and the maximum particle size of the micron-sized zero-valent iron is no greater than 100 μm.

4. The use according to claim 2, characterized in that: The activated carbon and micron-sized zero-valent iron are mixed in a mass ratio of 1:1 to 7:

1.

5. The use according to claim 2, characterized in that: The ball mill was operated for 12 hours at a rotation speed of 400 rpm and the ball milling atmosphere was air.

6. The use according to claim 2, characterized in that: During ball milling, the mass ratio of ball milling beads to the material being milled is 10:

1.

7. The use according to claim 6, characterized in that: The ball milling beads are made of zirconium oxide and have a diameter of 1-15 mm.

Citation Information

Patent Citations

  • Preparation method and application of mechanical milling modified iron-carbon material

    CN110065999A

  • Production method for preparing activated carbon loaded nano zero-valent pure iron powder and application thereof

    CN113634760A

  • Preparation method for preparing zero-valent aluminum and iron-based spinel composite material based on ball milling and application of zero-valent aluminum and iron-based spinel composite material

    CN114405612A

  • Ball-milling mixed type iron powder and preparation method and application thereof

    CN117483748A

  • Vulcanized micron zero-valent iron as well as preparation method and application thereof

    CN118341386A